MODEL PROJECT BASED LEARNING (PJBL) DENGAN METODE MIND-MAPPING DI SEKOLAH DASAR (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2024)
Project Based Learning (PjBL) is a learning model suggested in the independent curriculum, but teachers still encounter obstacles in applying this model in classroom learning. Project Based Learning (PjBL) integrated with the mind mapping method has the potential to develop high-level thinking skills including critical thinking, creative and problem solving, and mathematical communication of students. Besides that, Project Based Learning (PjBL) integrated with the mind mapping method can increase the effectiveness of learning for both teachers and students, where the Project Based Learning (PJBL) and Mind Mapping models are used as tools and media that can increase student learning activities and activities. This research aims to describe the steps of Project Based Learning (PjBL) through the mind mapping method in elementary schools, the principles of Project Based Learning (PjBL), the advantages and disadvantages of Project Based Learning (PjBL) and the characteristics of mind-mapping. By collecting data through literature study, this research is included in descriptive research. Keywords: Project Based Learning; Mind-Mapping; elementary school learning